DAMPAK PELATIHAN TERHADAP PENGETAHUAN MASYARAKAT MENGENAI PERAN DAN PENDIRIAN KOPERASI SYARIAH - Handoyo, Sarwo Edy; Setijaningsih, Herlin Tundjung (Transpublika Publisher, 2023)
Generally, economic inequality is found in rural areas. However, it can also occur in urban areas, such as in RW 08, Cibodas Village, Cibodas Subdistrict, Tangerang City, Banten. They generally experience difficulties in accessing the existing financial system. The requirements of financing institutions such as banks are difficult to fulfill because of their lack of skills and capital. Their lack of skills is due to their low level of education. As a result of low education, it is difficult to get a decent job and difficult to get financing from banks. The solution offered for some people like this is to be given training to find out the role of cooperatives including sharia cooperatives and the procedures for their establishment. This is because cooperatives are basically from, by and for members. The cooperatives referred to here can be savings and loan cooperatives, service cooperatives, trade and production cooperatives. By knowing the role and procedures for its establishment, it is hoped that difficulties in obtaining access to financing for the benefit of family and community economic development will find a way out. This training has proven to be able to increase community knowledge about the role of cooperatives and the procedures for their establishment